Wanting, and Weighting: White Women and Descriptive Representation in the 2016 Presidential Election. (30th January 2018) - Phillips, Christian
Abstract: This paper demonstrates that the relationship between wanting a descriptive representative based on gender, and giving that attitude weight in voting decisions, is weakest among White women voters. Among under-represented groups of voters, White women were uniquely positioned going into the 2016 presidential election—they had the option to choose "one of their own" in terms of race and gender. Yet, the majority did not vote for the White woman on the ballot, Hillary Rodham Clinton. This outcome is an opportunity to interrogate how descriptive representation functions in different ways across groups with distinct socio-political positions in American politics. I argue that the relationship between desiring descriptive representation, and giving it weight when deciding for whom to vote for, is different across groups. Using American National Election Survey (ANES) data, I show that this is the case in the 2016 election. Nearly two-thirds of White women who said that electing more women is important, voted for Trump. Moreover, White women's espoused belief in the necessity of electing more women had no significant effect on their ultimate vote choice. In contrast, the same desire for increased descriptive representation based on gender had large, positive, and significant effects on women of color's vote choice. This study bears on extant research considering descriptive representation's importance to voters based only on race, or gender, and on the broader literature linking group identities and voter behavior.